An Institute to promote the learning of aerial photography, which will promote the academic tourism in Portugal, help in the formation of destination image and promote sustainable tourism in Portugal. - Sheikh, Asma (2019)
This business plan is focused on promoting sustainable academic tourism and destination image of Portugal. Pixair Institute acts as a medium for achieving this by attracting international students, promoting student mobility and providing the students in Portugal the opportunity to, learn UAV pilot skills, aerial photography and enhance their career opportunities, maintaining sustainability by keeping the guiding principles required for economic, environmental and socio-cultural sustainability. Pixair focuses on providing attractive training services, with the cutting-edge equipment and expert staff, at a reasonable cost and flexible learning hours in the most attractive city of Portugal, Lisbon. The aim of Pixair is to combine the concept of achieving academic tourism by encouraging student mobility, and create destination image of Portugal, with aerial photography services through UAV, and promote Lisbon as a competitive destination for providing aerial photography and UAV pilot skills, compared to other institutes around the world. The plan focuses on analyzing the needs of Portugal, in terms of social, economic and environmental aspects and designing its structure and objectives required. Focusing on using an approach required for planning business model, such as Business Model Canvas determining the external market and internal environment by conducting questionnaires, competitor analysis and using it efficiently to plan effective strategies required for implementing the plan. Lastly designing a work plan and milestones required as a benchmark for analyzing the business financial projections for the next 5 years to determine the profitability and feasibility of Pixair. Pixair received a good response from students, photographers, and businesses for providing this opportunity in Portugal by promoting academic and sustainable tourism in Portugal by encouraging and promoting this new niche-segment of tourism in Portugal.